Building works and apprals for bridge / Fazillahanum Ab Rahim - Ab Rahim, Fazillahanum (2004)
Jabatan Kerja Raya Malaysia (JKR) is the technical arm of the Government of Malaysia and serves as the main implementing agency for development projects throughout the country. Established in 1872, JKR objectives is to develop the infrastructure and public utilities such as roads, water supplies, buildings, airports ,ports and jetties to meet the needs of the nation. The JKR implements development projects for various ministries, departments, statutory bodies and state governments.